Irisin regulates oxidative stress and mitochondrial dysfunction through the UCP2-AMPK pathway in prion diseases - Pei Wen; Zhixin Sun; Dongming Yang; Jie Li; Zhiping Li; Mengyang Zhao; DongDong Wang; Fengting Gou; Jingjing Wang; Yuexin Dai; Deming Zhao; Lifeng Yang (Cell Death and Disease)
Abstract Prion diseases are a group of fatal neurodegenerative disorders characterized by the abnormal folding of cellular prion proteins into pathogenic forms. The development of these diseases is intricately linked to oxidative stress and mitochondrial dysfunction. Irisin, an endogenous myokine, has demonstrated considerable neuroprotective potential due to its antioxidative properties. However, the protective effects of irisin against prion diseases have yet to be clarified. Our findings indicate that treatment with exogenous irisin can mitigate the apoptosis induced by PrP106–126. Additionally, irisin significantly reduces oxidative stress and alleviates the mitochondrial dysfunction triggered by PrP106–126. Furthermore, irisin treatment targets uncoupling protein 2 (UCP2) and activates the AMPK-Nrf2 pathway, substantially improving oxidative stress and mitochondrial dysfunction in N2a cells induced by PrP106–126. These results suggest that irisin represents a novel and promising therapeutic approach for treating prion diseases.